Envolvimento clínico e radiológico da coluna cervical em pacientes com artrite reumatoide - Leal, Geisa Maria Evangelista (2012)
Objective. To evaluate the prevalence of cervical spine (CS) involvement in patients with rheumatoid arthritis (RA) living in the northeast of Brazil. Methods. RA patients fulfilling the 1987 American College of Rheumatology criteria underwent physical and laboratory evaluation, including the Disease Activity Score (DAS28) and Health Assessment Questionnaire (HAQ). Hand and wrist radiographs, as well as CS radiographs in anteroposterior (open-mouth) and lateral (in neutral and full flexion) views were obtained. Neck length was measured clinically and radiologically. Results. There were 119 women and 13 men; mean age and disease duration were 52.3 + 12.7 and 10.2 + 6.9 years, respectively; 100 (76.1%) were rheumatoid factor (RF) positive. Mean DAS 28 and HAQ scores were 3.8 ± 1.2 and 1.14 ± 0.78, respectively, whereas Larsen’s index was 53.1 ± 30.8; 78% had a Larsen’s index < 80. Atlantoaxial subluxation was found in 52 (40%) patients, being lateral in 28 (21.5%), vertical in 16 (12.3%), anterior in 13 (10%), subaxial in 9 (6.9 %), and posterior in 1 (0.75%) patient. Use of Disease Modifying Drugs (DMARD) was irregular and only 6% were on biologics, despite 17.4 % presenting high DAS28. Subluxation was positively associated to greater Larsen’s index. Lateral AAS was associated to a longer neck length (p = 0.04). Conclusion. Despite irregular DMARD use, this cohort of RA patients displayed mild radiological damage both in peripheral joints and CS. Curiously, a shorter neck was associated to a lower risk of lateral subluxation.